Demographic, Clinical and Laboratory Parameters among Obese Children with Different Glycemic Status - Khadiza Tul Qubra; Mahjabin Rahman; Mahfuzur Rahman; Mohammad Tareq Imtiaz; Suraiya Begum (TAJ: Journal of Teachers Association, 2026)
Background: Childhood obesity is a growing public health concern worldwide and is strongly associated with insulin resistance, impaired glucose metabolism, and cardiometabolic complications. Data regarding glycemic status and insulin resistance among obese Bangladeshi children remain limited. Objective: This study aimed to evaluate the demographic, clinical and laboratory parameters of obese children according to glycemic status. Methods: This cross-sectional study was conducted in the Paediatric Endocrinology Division, Department of Paediadtrics, Bangladesh Medical University (former BSMMU), from 2021 to 2022. A total of 150 newly diagnosed obese children aged 6–18 years were enrolled using purposive sampling. Participants were categorized into euglycemia, prediabetes, and diabetes mellitus (DM) groups. Statistical analyses were performed using ANOVA and Chi-square tests, with p